2011
DOI: 10.1186/1477-7827-9-107
|View full text |Cite
|
Sign up to set email alerts
|

Comparative gene expression profiling of placentas from patients with severe pre-eclampsia and unexplained fetal growth restriction

Abstract: BackgroundIt has been well documented that pre-eclampsia and unexplained fetal growth restriction (FGR) have a common etiological background, but little is known about their linkage at the molecular level. The aim of this study was to further investigate the mechanisms underlying pre-eclampsia and unexplained FGR.MethodsWe analyzed differentially expressed genes in placental tissue from severe pre-eclamptic pregnancies (n = 8) and normotensive pregnancies with or (n = 8) without FGR (n = 8) using a microarray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
93
1
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(104 citation statements)
references
References 58 publications
6
93
1
4
Order By: Relevance
“…20 It has been reported that proliferation and apoptosis of trophoblasts are deregulated in preeclamptic placentas. [42][43][44] Interestingly, an increase in the mRNA of BCL6 in preeclamptic placentas has been observed independently by several groups, [21][22][23]26 yet its roles in the development of preeclampsia remain to be clarified. Recently, we have shown that BCL6 is indeed altered in preeclmaptic placentas, not only at its mRNA but also at its protein level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 It has been reported that proliferation and apoptosis of trophoblasts are deregulated in preeclamptic placentas. [42][43][44] Interestingly, an increase in the mRNA of BCL6 in preeclamptic placentas has been observed independently by several groups, [21][22][23]26 yet its roles in the development of preeclampsia remain to be clarified. Recently, we have shown that BCL6 is indeed altered in preeclmaptic placentas, not only at its mRNA but also at its protein level.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23][24][25][26] Its involvement in the pathogenesis remains to be defined. We have recently shown that BCL6 is increased in both mRNA and protein level in preeclamptic placentas.…”
Section: Introductionmentioning
confidence: 99%
“…From the Research Centre for Women's and Infants' Health BioBank, we collected 157 placenta samples (BioBank samples) with detailed clinical data from a range of hypertensive and normotensive states. To increase our sample size, the BioBank samples were then combined with the 7 previously published placental microarray data sets 4,5,[28][29][30][31][32] (Table S1 in the online-only Data Supplement) that we have previously analyzed in aggregate (Aggregate samples). 13 The final combined data set contained 330 placentas (157 PE and 173 non-PE) and expression values for 14 651 genes found in common across all original microarray platforms.…”
Section: Assembly Of the Combined Data Setmentioning
confidence: 99%
“…As a first step toward class discovery of PE pathology, we performed an aggregated analysis of 7 previously published human PE placental microarray data sets 4,5,[28][29][30][31][32] using unbiased/ unsupervised multivariate clustering techniques. 13 Our methods, which improve on similar approaches used for the molecular subclassification of tumors in the oncology field, 33,34 blindly group samples based solely on similarities in gene expression, independent of clinical characteristics.…”
mentioning
confidence: 99%
“…The mechanism of oxidative stress-mediated FGR is yet to be elucidated; it is generally believed that increased level of ROS induces a series of signal transduction mechanisms that eventually leads to apoptosis and various pathophysiological changes in the placenta leading to FGR [25].…”
Section: Discussionmentioning
confidence: 99%